2018
DOI: 10.1177/1741134318802605
|View full text |Cite
|
Sign up to set email alerts
|

Usability of theophylline extended-release dry syrups

Abstract: Objectives: We examined the usability of theophylline extended-release dry syrups, including their powder fluidity and ingestibility using one branded and six generic formulations (formulations A, B, C, D, E, F, and G, respectively). Methods: To evaluate the ease of handling by pharmacists, powder fluidity was evaluated by measuring the repose angle, whereas to determine ingestibility, the viewpoints of patients or caregivers were evaluated using a questionnaire survey. Results and discussion: The repose angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In addition, the cost price from wholesalers is not an optimal criterion for selecting formulations, thus warranting the selection on the basis of scientific assessments of usability. We previously examined the usability of branded and generic theophylline extended-release dry syrups from the viewpoints of both powder handling by pharmacists and patients or their assistants 8 ; the usability of each formulation was scientifically demonstrated to provide useful information for selecting branded or generic formulations. In addition, we concluded that information about taste and drug dissolution behaviors is required for individualized treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cost price from wholesalers is not an optimal criterion for selecting formulations, thus warranting the selection on the basis of scientific assessments of usability. We previously examined the usability of branded and generic theophylline extended-release dry syrups from the viewpoints of both powder handling by pharmacists and patients or their assistants 8 ; the usability of each formulation was scientifically demonstrated to provide useful information for selecting branded or generic formulations. In addition, we concluded that information about taste and drug dissolution behaviors is required for individualized treatments.…”
Section: Introductionmentioning
confidence: 99%